Michael j. Sandel, Tyrania merytokracji. Co się stało z dobrem wspólnym? Wydawnictwo Naukowe PWN, Warszawa 2020, ss. 362 - Stawska, Marta (Studia Edukacyjne, 2022)
Michael j. Sandel, Tyrania merytokracji. Co się stało z dobrem wspólnym? Wydawnictwo Naukowe PWN, Warszawa 2020, ss. 362